Proposed training program for the development of flexibility for students of primary empirical research to develop a flexible shoulder joint and spine and hip - Mohammed, Sundus (Journal of Physical Education, 2019)
A Suggested training program to develop the flexibility of primary pupils aged 10years old an experimental research to develop flexibility of the shoulder, vertebra and hip joint the research aims to identify the effect of suggested program to develop flexibility of 10 year old pupils in the shoulder ,vertebras and hip joint it was hypnotized the existence of significant differences between experimental and controlled group within the joints mentioned 10 pupils of the fourth grade primary were the subject s the study occluded that there exists significant differences in the flexibility of the shoulder, vertebra and the hip between pre and post tests and for the latter test for the e complex movements be an emphases on the correct performance that should be based on sound empirical